Efficiency of phototherapy in patients with mycosis fungoides: preliminary results of a comparative non-randomized study - A. E. Karamova; M. B. Zhilova; L. F. Znamenskaya; A. A. Vorontsova (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Clinical reasoning. There is a need to optimize the use of UV-B-311 nm and PUVA-therapy in patients with mycosis fungoides to determine the duration of the treatment regimen, the number of sessions per week, and ultraviolet irradiation regimen. Goal of research. Evaluation of the effect of the type and duration phototherapy on efficacy in patients with mycosis fungoides. Principle. A comparative, non-randomized study of the effectiveness of phototherapy in patients with mycosis fungoides in the early stages. Evaluation of the effectiveness of UV-B-311 nm and PUVA therapy was performed using the BSA index (area of skin lesions) and Modified Severity-Weighted Assessment Tool (mSWAT), as well as according to the criteria proposed by the International Society for Skin Lymphomas (ISCL), the European Organization for the Study and Cancer Treatment (EORTC) and United States Cutaneous Lymphoma Consortium (USCLC). Results. The study included 14 patients with mycosis fungoides, 5 of whom received treatment with UV-B-311 nm, 9 PUVA therapy. A strong correlation was found between the duration of UV-B-311 nm therapy with mSWAT delta (R = 0.90; p = 0.038) and BSA delta (R = 0.90; p = 0.038), while similar correlation was not found in the PUVA-therapy group (mSWAT (R = 0.24; p = 0.527); BSA (R = 0.09; p = 0.823)). When comparing the effectiveness of therapy between the treatment group UV-B-311 nm and PUVA therapy, delta mSWAT and BSA at the 20th procedure, delta mSWAT and BSA after the end of therapy did not have a statistically significant difference between the UVB-311 nm and PUVA groups. Conclusion. Statistically significant correlation was found between the number of procedures and the effectiveness of therapy In the UV-B-311 nm group. An increase in the number of PUVA therapy procedures (after 20) does not lead to a statistically significant increase in the effectiveness of treatment. Additional research is needed to increase the level of evidence of the results and develop optimal phototherapy regimens.